Effects of Enteromorpha prolifera polysaccharide on intestinal health of spotted sea bass Lateolabrax maculatus - Zhongying Long; Longhui Liu; Huihui Qin; Sishun Zhou; Lumin Kong; Jianrong Ma; Hao Lin; Zhangfan Huang; Yi Lin; Zhongbao Li (Aquaculture Reports)
Enteromorpha prolifera polysaccharide (EPP) is a kind of seaweed polysaccharide with outstanding biological activity. In this study, a 49-day culture trial was conducted to explore the effects of dietary EPP on intestinal health in spotted sea bass. Six experimental diets containing 0, 3, 6, 9, 12, and 15 g/kg EPP were formulated. A total of 540 similarly sized and healthy spotted sea bass were randomly assigned to 6 groups and fed the respective diet. The results showed that dietary EPP supplementation significantly improved the activity of digestive enzymes, including amylase, lipase, and trypsin, and reduced the permeability of the intestinal mucosa, which was shown to significantly reduce the content of D-lactic acid and the activity of diamine oxidase in serum. On the other hand, intestinal villi length and muscle thickness increased significantly, and intestinal tissue morphology improved. Dietary EPP also changed intestinal microbial composition, increased Firmicutes abundance, and increased intestinal microbial diversity. Transcriptome results suggest that EPP may improve intestinal tissue morphology and intestinal barrier function by up-regulating tight junction protein 1 (TJP1) and zona occludens 1 (ZO-1) genes, thereby improving intestinal health. In addition, significant changes in several inflammatory factor genes were observed. EPP may have enormous potential for regulating immune and inflammatory responses. In conclusion, dietary EPP can significantly improve the intestinal health of spotted sea bass.